Impact of a moulded pureed diet on taste, appearance, recognisability, and overall liking among patients in an acute hospital - Lam, Calvin Jun Yan; Phua, Quan Quan; Guo, Emily Yiting; Sia, Isaac Kwee Mien (Frontiers in Nutrition, 2023)
Hospital meals potentially influence patients’ nutritional, physical, and emotional well-being during their admission. Patients on pureed diets report poorer meal satisfaction, due to taste, appearance, and recognisability, potentially impacting on their nutritional status. This study compared whether a moulded pureed diet made from modified maize starch led to improved taste, appearance, recognisability, and overall liking, compared to an unmoulded pureed diet made from potato starch in an acute hospital. Patients on texture-modified diets were recruited and presented with two pureed diets – unmoulded and moulded. Participants were asked to identify meat and vegetable dishes prior to eating. After the meal, participants indicated their diet preference in terms of appearance, taste, and overall liking. 145 participants were recruited, of which 126 completed data collection. 86% correctly identified moulded meat dishes, 69% correctly identified moulded vegetable dishes, with an overall 77% accuracy in identifying moulded puree side dishes. On unmoulded puree side dishes, participants correctly identified 25% of meat dishes, 4% of vegetable dishes, with an overall accuracy of 14%. In terms of preference, the moulded puree was preferred, with 81% for appearance, 76% for taste and 75% for overall preference. When participants had differing preferences for appearance and taste (e.g. prefers unmoulded puree appearance and moulded puree taste), 95% of them subsequently aligned their overall preference with their taste preference (i.e. overall preferred moulded pureed diet). This suggests that taste has a stronger influence on overall preference compared to appearance. Findings indicate that a moulded pureed diet made from modified maize starch led to improved recognisability, taste, appearance, and overall liking compared to an unmoulded pureed diet made from potato starch. Taste had a stronger influence on overall preference compared to appearance. These findings capture patient preferences and may have implications on how hospital pureed diets may be improved, potentially improving patient nutrition and health outcomes.